The Wilkes Land Anomaly revisited. Issue 3 (14th January 2015) - Weihaupt, John G.; Van Der Hoeven, Frans G.; Chambers, Frederick B.; Lorius, Claude; Wyckoff, John W.; Castendyk, Devin
Abstract: The Wilkes Land Gravity Anomaly, first reported in 1959–60, is located in northern Victoria Land in the Pacific Ocean sector of East Antarctica, 1400 km west of the Ross Sea and centred at 70°00'S-140°00'E. Initially described on the basis of ground-based seismic and gravity survey, and estimated at the time to have a diameter of 243 km, the original data are now supplemented by data from airborne radiosound survey, airborne gravity survey, airborne magnetic survey and satellite remote sensing. These new data enable us to expand upon the original data, and reveal that the structure has a diameter of some 510 km, is accompanied by ice streams and a chaotically disturbed region of the continental ice sheet, has a subglacial topographical relief of ≥1500 m, and exhibits a negative free air gravity anomaly associated with a larger central positive free air gravity anomaly. The feature has been described as a volcanic structure, an igneous intrusion, an ancient igneous diapir, a subglacial sedimentary basin, a glacially eroded subglacial valley, a tectonic feature and a meteorite impact crater. We re-examine the feature on the basis of these collective data, with emphasis on the free air gravity anomaly signs, magnitudes and patterns, magnetic signature magnitudes and patterns, and the size, shape, dimensions and morphology of the structure. This enhanced view adds substantially to the original description provided at the time of discovery, and suggests several explanations for the origin of the Wilkes Land Anomaly. However, the importance of this feature lies not only in determining its origin but by the fact that this part of the Wilkes Subglacial Basin is one of the most prominent regional negative geoid and associated gravity anomalies of the Antarctic continent.